Proverb: Nearly Spring in a New Hampshire Barn - Randall, Regine (On and Off the Road: Poems of New Hampshire, 2020)
"This poetry anthology, with poems from poets throughout New England and from other states - is a result of Peterborough Poetry Project's second poetry contest. We invited poets, writers, and observers to submit up to three poems about New Hampshire - past, present, future, or fantasy. Forty-eight poems from the contest form this book. The poems are in three different sections by themes: People, Places, and The Wild, but readers may find that several poems have more than one theme. A poem may appear to be about nature, but also our reactions to it. Another poem may appear to be true, but might be pure fantasy. Such is the nature of poetry: read it for the obvious, then read it again to see if more reveals itself"–Back cover
Google-Books-ID: 9QSYzQEACAAJ
Keywords: dept.cur; literary-poetry

One Story Creates Another: Using Book Clubs to Promote Inquiry in the Content Areas - Randall, Regine E.; Marangell, Joseph P. (ie: inquiry in education, 2020)
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

Experimental critical qualitative inquiry: Disrupting methodologies, resisting subjects - Marn, Travis M.; Wolgemuth, Jennifer R. (Post-Qualitative Research and Innovative Methodologies, 2020)
Keywords: dept.cur; ⛔ No DOI found

Axes of support: Explicit to implicit and practical to epistemic - Fick, S.J.; Arias, A.M.; Vo, T.; Sherwood, C.-A.; Benedict-Chambers, A.; Lo, A.S. (Comput. -Supported Collab. Learn. Conf., CSCL, 2020)
Drawing from analyses of teaching and learning, we posit a theoretical framework of axes, practical to epistemic and explicit to implicit, which frame four quadrants of support needed to know how and why to use the crosscutting concepts in sensemaking. This work has implications for the design of learning environments that use the crosscutting concepts in scientific sensemaking. © ISLS.
Journal Abbreviation: Comput. -Supported Collab. Learn. Conf., CSCL
Keywords: Computer aided instruction; Four quadrant; Learning environments; Sensemaking; Teaching and learning; Technology transfer; Theoretical framework; dept.cur

Changing What We Might Have Done on Our Own: Improving Classroom Culture and Learning through Teacher Collaboration - Randall, Régine; Marangell, Joseph (The Clearing House: A Journal of Educational Strategies, Issues and Ideas, 2020)
Student achievement is not always the equivalent of what students learn, especially when educators use their feedback to shape daily instruction. When students share their classroom experiences, we can determine better ways to create interdisciplinary partnerships, manage workload, enhance historical understandings, and communicate conclusions. Being able to trust in what students are doing in class, how well they are doing it, and what they will be able to do motivated the authors, who are two veteran educators, to reevaluate when their own teaching seemed most effective. What they discovered is incongruent with the traditional delivery of instruction by a single teacher. The authors found that their collaboration as co-teachers not only benefited their students but increased their own professional learning in terms of pedagogy, content knowledge, and the use of disciplinary literacy.
_eprint: https://doi.org/10.1080/00098655.2020.1828240
Keywords: Co-teaching; dept.cur; interdisciplinary partnerships; peer-reviewed; professional collaboration; secondary education; student engagement

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
tex.ids: sinclairBecomingAlliesAccomplices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084794698 type: Article
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Responding to Heteronormativity: Lesbian, Gay, Bisexual and Asexual Preservice Teachers’ Dreams and Fears - Bower-Phipps, Laura (Current Issues in Education, 2020)
Heteronormativity, the “privileging of heterosexuality through its normalization” (Jackson, 2006, p. 109), causes confusion and anxiety for many lesbian, gay, bisexual, and asexual preservice teachers as they consider how they will talk about their lives with students. This article explores how preservice teachers have experienced the normalization of heterosexuality and the ways in which these experiences will shape their professional practices. Focus group and follow up interviews with lesbian, gay, bisexual, and asexual preservice teachers were analyzed using a constant comparison method. Findings suggest that participants’ professional vision was largely a response to heteronormativity. They wanted to be out, be role models, and create safe spaces; yet they felt unable to achieve this vision in what they perceived as heteronormative school climates. Implications for teacher preparation programs and policies include the importance of equipping all preservice teachers to identify and disrupt heteronormativity in schools.
Number: 1
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

“The Goals Remain Elusive”: Using Drawings to Examine Shifts in Teachers’ Mental Models Before and After an NGSS Professional Learning Experience - Sherwood, Carrie-Anne (Journal of Science Teacher Education, 2020)
Teachers’ ability to effectively enact the ambitious vision of the NGSS depends on their understanding of the conceptual and instructional shifts required, and their interpretation of how to implement these shifts in their classrooms. Thus, understanding teachers’ practical knowledge regarding the shifts is an important step in supporting them to effectively implement the NGSS vision. This study used a mental models framework and teacher drawings to examine the practical knowledge of 22 in-service secondary science teachers before and after professional development that was designed to support them to understand and make incremental instructional shifts aligned with the NGSS. Findings indicate that teachers’ mental models shifted in two promising ways. First, teachers recognized that their roles and their students’ roles would need to change, and second, the doing of science looks and sounds different than what was traditionally done in their classrooms. However, findings also suggest that teachers struggled to reconcile new ideas from the PD with their previous mental models of their classroom practice. These findings are significant because they indicate, teachers may have more fully-formed mental models for what science teaching and learning looks and sounds like when it is focused on what most would traditionally think of as classroom science doing (e.g., “doing labs”), or when it includes traditional knowledge dissemination structures (e.g., lectures). This has important implications for science teacher educators and researchers, which will be discussed. © 2020, © 2020 Association for Science Teacher Education.
2 citations (Crossref) [2023-10-31] tex.ids: sherwoodGoalsRemainElusive2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088064339 type: Article
Keywords: NGSS; Science teacher education; dept.cur; mental models; peer-reviewed; professional development; teacher drawings; teacher practical knowledge